Evaluasi Dampak Inflasi Terhadap Perekonomian Menurut Perspektif Syariah Islam pada Era Globalisasi Modern - M. Fahri Manurung; Nur Afni Zahara; Rinjani Balqis Salsabila; Muhammad Arfan Harahap (Universitas 45 Surabaya, 2025)
Inflation is an economic phenomenon that has a significant impact on the stability of national economies, especially in the modern era of globalization characterized by highly interconnected markets and increasingly complex price dynamics. From the perspective of Islamic Sharia, inflation is not viewed solely as an economic issue but is also closely related to ethics, distributive justice, and balance within financial and commercial transactions. This study aims to evaluate the impact of inflation on the economy using Islamic principles, including the prohibition of riba, gharar, and ihtikar, which are often associated with price instability. The research also examines how the concept of intrinsic value of money and market mechanisms in Sharia can offer solutions to reduce economic distortions caused by inflation. In the context of globalization, international economic interactions frequently create external pressures that influence domestic inflation levels. Therefore, understanding Sharia-based economic strategies becomes essential to maintaining price stability, protecting purchasing power, and ensuring a fairer distribution of wealth. The findings of this study are expected to contribute to the development of more sustainable economic policies aligned with Islamic principles.